Immunomodulatory Effects of Calcium and Strontium Co-Doped Titanium Oxides on Osteogenesis - Yuan, Xiangwei; Cao, Huiliang; Wang, Jiaxing; Tang, Kaiwei; Li, Bin; Zhao, Yaochao; Cheng, Mengqi; Qin, Hui; Liu, Xuanyong; Zhang, Xianlong (Frontiers in Immunology, 2017)
The effects of calcium (Ca) or strontium (Sr) on host osteogenesis and immune responses have been investigated separately. In clinical practice, these two elements may both be present around an orthopedic device, but their potential synergistic effects on osteogenesis and the immune response have not been explored to date. In this work, we investigated the immunomodulatory effects of Ca and Sr co-doped titanium oxides on osteogenesis in vitro using the mouse macrophage cell line RAW 264.7 alone and in co-culture with mouse bone mesenchymal stem cells (BMSCs), and in vivo using a mouse air-pouch model. Coatings containing Ca and Sr at different concentration ratios were fabricated on titanium substrates using micro-arc oxidation and electrochemical treatment. The in vitro and in vivo results demonstrated that the Ca and Sr concentration ratio has a marked influence on macrophage polarization. The coating with a Ca/Sr ratio of 2:1 was superior to those with other Ca and/or Sr concentrations in terms of modulating M2 polarization, which enhanced osteogenic differentiation of mouse BMSCs in co-culture. These findings suggest that the osteoimmunomodulatory effect of a titanium-oxide coating can be enhanced by modulating the concentration ratio of its components.